Time - No, Hyeong-u ca. 20. Jh (Palisade Tartan, 2010)
"Attractive Seh-hee is having problems with her boyfriend, Ji-woo. After two years, their love has entered a period of weariness. Though faithful to his fiancée, Ji-woo eyes other women and, in bed, seems to get excited only at the thought of making love to other partners. Seh-hee can't cope with the mounting jealousy tainting her life and decides to dramatically change her look - to become a new woman, with whom her boyfriend can again fall in love. She enters a plastic-surgery clinic and then vanishes for six months - long enough for the scars to heal - leaving Ji-woo hurt and confused by her disappearance. Resurfacing as the new waitress at the coffee shop Ji-woo frequents, Seh-hee - now calling herself See-hee? tries to seduce him. [...]" [filmdienst.de]
Original: Südkorea, Japan 2006
Scene selection ; making of ; trailer
Keywords: Film; DVD-Video